2013
DOI: 10.1093/eurheartj/eht207
|View full text |Cite
|
Sign up to set email alerts
|

Quarterly vs. yearly clinical follow-up of remotely monitored recipients of prophylactic implantable cardioverter-defibrillators: results of the REFORM trial

Abstract: AimsThe rapidly increasing number of patients with implantable cardioverter-defibrillators (ICD) places a large burden on follow-up providers. This study investigated the possibility of longer in-office follow-up intervals in primary prevention ICD patients under remote monitoring with automatic daily data transmissions from the implant memory.Methods and resultsConducted in 155 ICD recipients with MADIT II indications, the study compared the burden of scheduled and unscheduled ICD follow-up visits, quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 28 publications
1
71
1
5
Order By: Relevance
“…Remote monitoring permits an earlier reaction to events requiring physician intervention in comparison to regular in-office device checks, with 98.6% of transmissions being reviewed within two working days in our cohort. (3,4,6,(14)(15)(16)(17)(18)(19)(20)(21) Early detection allows prompt management of arrhythmias, early management of device malfunction and device reprogramming to reduce inappropriate defibrillator shocks. (18,22,23) Compliance to remote monitoring was good, with an overall missed transmission rate of 11.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote monitoring permits an earlier reaction to events requiring physician intervention in comparison to regular in-office device checks, with 98.6% of transmissions being reviewed within two working days in our cohort. (3,4,6,(14)(15)(16)(17)(18)(19)(20)(21) Early detection allows prompt management of arrhythmias, early management of device malfunction and device reprogramming to reduce inappropriate defibrillator shocks. (18,22,23) Compliance to remote monitoring was good, with an overall missed transmission rate of 11.8%.…”
Section: Discussionmentioning
confidence: 99%
“…(5,6) In addition, patient compliance to scheduled remote monitoring evaluation is superior compared to in-office checks. (5) Home monitoring is relatively new in Southeast Asia, (1,7) with pickup rates increasing over recent years.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recently, the REFORM trial compared the burden of scheduled and unscheduled ICD follow-up visits, quality of life (QOL) by means of the SF-36 questionnaire, and clinical outcomes in patients randomized to either 3-or 12-month follow-up intervals. 8 The total rate of follow-up visits was reduced by 58% and there was a favorable impact on the patients' QOL because of a longer follow-up interval, although the 12-month follow-up interval resulted in a slight increase of in-office ICD follow-ups and more patients were lost to follow-up in the 12-month group. In addition, the REFORM trial found no difference in the morbidity and hospitalization rates between the 2 groups as did the TRUST 5 and COMPAS 6 trials, in which no difference was found in major adverse events between the conventional follow-up group and the Home Monitoring group.…”
Section: Article P 2704mentioning
confidence: 91%
“…W tym czasie QoL chorych objętych rutynowym schematem opieki kardiologicznej (planowe wizyty w poradni raz na 3 miesiące) pogorszyła się [62]. Natomiast Al-Khatib i wsp.…”
Section: Nowoczesne Formy Zdalnego Kontrolowania Icd a Jakość żYciaunclassified